Facing COVID-19 in Liberia: Adaptations of the Resilient and Responsive Health Systems Initiative. Issue 1 (8th October 2021) - Marsh, Regan H.; Plyler, Chelsea; Miller, Mary; Klar, Robin; Adeiza, Mukhtar; Wachekwa, Ian; Koomson, Freda; Garlo, James Luke; Kruah, Kebeh; Lake, Sodey C.; Matte, Rita; Cook, Rebecca; et al.
The 5-year Resilient and Responsive Health Systems (RRHS)-Liberia Initiative, funded by PEPFAR via HRSA, launched in 2017 and was designed to support the implementation of Liberia's National Health Workforce Program as a means to improving HIV-related health outcomes. The COVID-19 pandemic, arrived in Liberia just five years after Ebola and during RRHS-Liberia's fourth year, impacted educational programs and threatened the project's continued work. This paper presents the challenges that the COVID-19 pandemic posed to the RRHS partners, as well as adaptations they made to maintain progress towards project goals: 1) contributing to Liberia's 95-95-95 HIV targets via direct service delivery, and 2) building a resilient and responsive health workforce in Liberia via instruction and training. Direct health service impacts included decreased patient volumes and understaffing; adaptations included development of and trainings on safety protocols, provision of telehealth services, and community health worker involvement. Instruction and training impacts included suspension of in-person teaching and learning; adaptations included utilization of multiple online learning and virtual conferencing tools, and increasing clinical didactics in lieu of bedside mentorship. The RRHS team recommends that these adaptations be continued with significant investment in technology, IT support, and training, as well as close coordination among partner institutions. Ultimately, the RRHS Liberia consortium and its partners made significant strides in response to ensuring ongoing education during the pandemic, an experience that will inform continued service delivery, teaching, and learning in Liberia.